Peran Otoritas Jasa Keuangan dalam Mengawasi Arus Pasar Modal di Indonesia - Defril Hidayat; Ari Bakti Windi Aji; Muhammad Ibrahim Aziz (Fakultas Hukum, Universitas Muslim Indonesia, 2022)
This study aims to examine the enforcement of laws and the role of the Financial Services Authority in addressing capital market violations amid the development of economic flows in Indonesia. This study uses normative legal research with the statute and comparative approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that capital market violations consist of administrative violations and criminal offenses. Meanwhile, Bapepam’s role in addressing capital market violations has been shifted to the Financial Services Authority. OJK is a builder, regulator, and supervisor of capital market activities. In executing its law enforcement functions, OJK also has the authority to examine, impose administrative sanctions, and investigate criminal offenses to be pursued and resolved through the criminal justice system. On the other hand, based on the una via principle, OJK can also decide not to proceed to the investigation stage of an alleged criminal offense by imposing an administrative sanction in the form of a fine accompanied by a written order. In carrying out its enforcement functions, OJK enforces criminal law both preventively and repressively. Therefore, it is recommended that the OJK and relevant parties enhance coordination and collaboration in enforcing capital market laws, both preventively and repressively. This enforcement can be achieved by improving human resources capacity and infrastructure to monitor daily capital market activities. Increasing investor education and awareness is also crucial to reduce the likelihood of violations. Lastly, OJK should ensure a balanced approach between preventive and repressive law enforcement, considering the una via principle in specific cases. Implementing these recommendations will support creating a conducive, transparent, and fair capital market environment, ultimately attracting investors and further promoting Indonesia’s economic growth.